Aduceti la forma ce mai simpla :
3(√12-2√27)
√48-2√3(2-5√12)
(3+√3)(2+√3)
Răspunsuri la întrebare
Răspuns de
1
3(√12-2√27) =
=3(2√3-6√3) =
=3(-4√3) =
=-12√3
√48-2√3(2-5√12)=
= 4√3-2√3(2-10√3)=
=4√3-4√3+60=
=60
(3+√3)(2+√3) =
=6+2√3+3√3+3=
=9+5√3
=3(2√3-6√3) =
=3(-4√3) =
=-12√3
√48-2√3(2-5√12)=
= 4√3-2√3(2-10√3)=
=4√3-4√3+60=
=60
(3+√3)(2+√3) =
=6+2√3+3√3+3=
=9+5√3
Răspuns de
0
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă